BIOCONTROL FOR RHIZOCTONIA STEM ROT DISEASE BY USING COMBINATION OF SPECIFIC ENDOPHYTE IN PADDY TIDAL SWAMP - Budi, Ismed Setya; Mariana, Mariana (AGRIVITA, Journal of Agricultural Science, 2013)
The use of combination of specific endophytic in tidal swamps to control stem root disease as biological control agents has not been done. It is expected that this combination is able to continuously protect plants from pathogen interference. The research was carried out in type C tidal swamp in Banjar regency of South Kalimantan, from March to November 2011, temperature 29-32oC, and pH 4.0-5.5. The method used was Split Plot design. Biocontrol preparation for both types of endophytic was applied in seeds in 7 days after planting (DAP). Observation on high intensity and plant diseases of planting stage on tidal swamps (taradak, ampak and lacak) was conducted. The results showed that there was a reduction of disease ranging from 58.70 to 87.29%. The application of combination of two biocontrol agents (T. viride PS-2.1 + P. fluorescent PS-4.8), (Fusarium non-pathogenic PS-1.5 + P. fluorescent PS-4.8) and (T. viride PS-2.1+ FNP PS-1.5) isolate gave the best inhibition result, reduced disease intensity, and increased plant height. The result of soil analysis before and after application of endophytic showed that there was an increase in soil fertility with the element addition of N, P, K and pH. Keywords: stem rot, endophytic combination, paddy, tidal swamp